EFEKTIVITAS SISTEM E-COURT DI PENGADILAN NEGERI LUBUK BASUNG - Julisman, Romi; Rahmayani, Nuzul; Nazar, Jasman (Collegium Studiosum Journal, 2023)
Technological developments are getting faster and faster, driving changes that occur in the wider community. As a result of these technological developments, the world of justice must also innovate to keep up with current developments. Therefore the Supreme Court created the E-COURT application, a website system that operates in a network to make it easier for courts to resolve civil cases. The purpose of this writing is to find out how the Lubuk Basung District Court maximizes the implementation of the Perma issued by the Supreme Court and to find out the factors that become obstacles in e-court proving. This research method is descriptive analysis, that is, from research it is expected to obtain a detailed and systematic description of the problem to be studied. In this study, using the type of empirical approach research. The empirical approach is research that is used to describe conditions seen in the field as they are. That the Lubuk Basung Court has used e-court trials in a hybrid manner to minimize the deficiencies that exist in the e-court itself. However, these changes do not necessarily improve everything, there are still many obstacles in this hybrid e-court and the ineffective implementation of e-court at the Lubuk Basung District Court.